Problemy samorządności w reformie gospodarczej - Wierzbicki, Janusz (Wydział Prawa i Administracji UAM, 1982)
The author takes into consideration self-government problems of state enterprises and local administration, that arise from realization of the economy reform in conditions of deep economic and political crisis. The author assumes that independence of state enterprises is the basic premise for overcoming the economic crises in a several years' period of economy stabilizing. In that period internal equilibrium would be redressed. The author points out, however, that enterprise independence does not seem to be possible as long as inflation is increasing. In such conditions it is not possible to ensure rational functioning for enterprises. After reduction of inflation gap, in a range indispensable, for ensurance effective activities for enterprises, it will be possible to proceed to the reform aiming at- decentralization of economic system as well as redressing the equilibrium. Introduction of self-government into enterprises ought to conduce to easier population approval of sacrifices connected with antiinflation policy. The role of that self-government in directing enterprises might be definitely stated aliter realization of the reform, in a longer period of stabilizing the economy. The author considers local self-government in another aspect, explaining first of all, why people's councils which have been functioning since 1950 do not meet requirements of self-government local administration. The author pays attention to the fact that the lack of real local self-government results from unsatisfactory democratization of people's councils. That influences unfavourably not only the satisfaction of local needs but also the enterprises economy, leads to increase of political pressure on workers' self-government and is aversed to the effectiveness increase in their economic activity.
Problems of Self-Government in the Economy Reform